1994
DOI: 10.1002/bjs.1800810839
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative endoscopic drainage for malignant obstructive jaundice

Abstract: The role of preoperative endoscopic drainage for patients with malignant obstructive jaundice was evaluated in a randomized controlled trial. A total of 87 patients were assigned to either early elective surgery (44 patients) or endoscopic biliary drainage followed by exploration (43). Thirty-seven patients underwent successful stent insertion and 25 had effective biliary drainage. Complications related to endoscopy occurred in 12 patients. After endoscopic drainage significant reductions of hyperbilirubinaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
152
0
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(160 citation statements)
references
References 21 publications
2
152
0
6
Order By: Relevance
“…The flow of references is shown in Figure 1 (PRISMA flow diagram) (Moher 2009). In total, 14 references described six completed randomised clinical trials that fulfilled the inclusion criteria (Hatfield 1982;McPherson 1984;Pitt 1985;Lai 1994;Wig 1999;. A total of 520 patients randomised to pre-operative biliary drainage (265 patients) versus no pre-operative biliary drainage (255 patients) were included in the six trials.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The flow of references is shown in Figure 1 (PRISMA flow diagram) (Moher 2009). In total, 14 references described six completed randomised clinical trials that fulfilled the inclusion criteria (Hatfield 1982;McPherson 1984;Pitt 1985;Lai 1994;Wig 1999;. A total of 520 patients randomised to pre-operative biliary drainage (265 patients) versus no pre-operative biliary drainage (255 patients) were included in the six trials.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Included studies-Four trials used percutaneous transhepatic biliary drainage as the method of drainage (Hatfield 1982;McPherson 1984;Pitt 1985;Wig 1999). Two trials used endoscopic sphincterotomy as the method of drainage (Lai 1994;.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Only two prospective studies have attempted to addresses this issue and one showed a benefit in the pre-operative drainage group. 37,38 The randomised study of Lygidakis et al 37 compared patients undergoing pancreaticoduodenectomy. Nineteen received an endoscopic stent and 19 no intervention prior to surgery.…”
Section: The Clinical Datamentioning
confidence: 99%